A Practical System for Pig Farm Wastewater Treatment - Pairin, Jirayu; Rachdawong, Pichaya; Nuengchamong, Chackrit (วารสารวิชาการ โรงเรียนนายร้อยพระจุลจอมเกล้า, 2019)
High rate of pig farm growth has been observed during these recent years. In 2017, 10.19 million head count of pig was raised in Thailand. In the same year, about 57 odor and 10 wastewater complaints were filed against pig farm owners. This prompted concerns from government and the Internal Security Operations Command (ISOC) to look into this problem seriously. Piggery wastewater is known to be high in organics, solids, as well as rich nutrient content such as nitrogen and phosphorus. In this study, we investigated the performance of a system consisting of a presettling tank and a three-compartment anaerobic baffled (ABR) reactor to treat pig farm wastewater under low and high flow rate condition. An experiment was run for 80 days at a demonstration farm of the Faculty of Veterinary Science in Nakhon Pathom province. The performance for total COD removal was between 50-78 percent and majorities of organics and solids removal was by sedimentation. The efficiencies of sedimentation process, however, can be very sensitive to solids accumulation and washout. The average TKN removal was only 25 percent. The low removal efficiency was due to the fact that majority of TKN was soluble and the soluble part of TKN cannot be removed properly in anaerobic process. When considering the PCD standard for pig farm, the system still needed an improvement, with respect to total COD and TSS concentrations in the effluent. Enlargement of a presettling tank or an additional presettling unit with solids drainage ports could be a practical option for better solids and organics treatment.